The Liberation of Method : The Ethics of Emancipatory Biblical Interpretation - Janzen, David, 1968- (Book collections on Project MUSE., 2021)
The field of biblical studies has championed the historical-critical method as the only way to guarantee objective interpretation. But in recent decades, scholars have pursued hermeneutical approaches that provide interpretations useful for marginalized communities who see the Bible as a resource in their struggles against oppression. Such liberative strategies remain on the margins. The Liberation of Method argues that this marginality must end, and that liberative methods should become central to biblical studies.